2007
DOI: 10.1007/s10620-007-9769-5
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Gastric Ulcer Healing by Alendronate, a Nitrogen-Containing Bisphosphonate, in Rats

Abstract: Bisphosphonates such as alendronate have been developed as antiresorptive agents capable of treating diseases related to bone remodeling. In the present study, we examined the effect of alendronate on the healing of acetic acid-induced gastric ulcers in rats and investigated the mechanism involved in this action both in vivo and in vitro using the rat gastric epithelial cell line (RGM1). Acetic acid-induced gastric ulcers healed spontaneously, with up-regulation of COX-2/prostaglandin E2 production as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Indomethacin, a non steroidal anti-infl ammatory drug, delayed the healing of experimental gastric ulcers in rats, concomitant with down-regulation of such growth factors as well as suppression of the angiogenic response (Amagase et al, 2003;2006). Chakroborty et al (2004) reported that dopamine signifi cantly inhibited the VEGF-mediated angiogenesis in rat malignant gastric tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Indomethacin, a non steroidal anti-infl ammatory drug, delayed the healing of experimental gastric ulcers in rats, concomitant with down-regulation of such growth factors as well as suppression of the angiogenic response (Amagase et al, 2003;2006). Chakroborty et al (2004) reported that dopamine signifi cantly inhibited the VEGF-mediated angiogenesis in rat malignant gastric tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Amagase et al (1) showed previously that bFGF is essential for angiogenesis in the healing of gastric ulcers induced by alendronate. In addition, Ernst et al (8) demonstrated that local injection of bFGF to the base of gastric ulcers significantly accelerated healing, in association with an increase in the amount of microvasculature and mucosal blood flow in the ulcerated area.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Elliott et al [11] reported that BPPs at relatively low doses exert a deleterious influence on the healing of gastric ulcers and potentiated the healing impairment action of NSAIDs, frequently prescribed together with BPPs in patients with arthritis or osteroprosis. We also found that alendronate delayed the healing of gastric ulcers in rats, with concomitant impairment of vasculariza tion/granulation at the ulcer base [9,12,13]. Because the mechanism underlying these adverse reactions of BPPs remains unclear, an effective therapy for the prevention of these side effects is not currently available.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, it was also shown that rebamipide increases mucosal prostaglandin (PG) production and mucus secretion, the important factors contributing to the mucosal defensive ability [20,21]. We have reported the beneficial influences of this agent on the adverse reactions induced in the stomach by alendronate [9,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation